Abstracts - Zamora, Centli (Facultad de Arquitectura, Universidad Nacional Autónoma de México, 2023)
With this edition, Bitácora architecture joins to the celebrations for the 70th anniversary of the “dedication” of Ciudad Universitaria (CU), on November 20 1952, as well as for the fifteenth anniversary of the inclusion of its central campus in the list UNESCO World Heritage.